Developing the Horizons of the Mind : Relational and Contextual Reasoning and the Resolution of Cognitive Conflict. - Reich, K. Helmut (Cambridge University Press, 2002)
Developing the Horizons of the Mind is the first book on Relational and Contextual Reasoning (RCR), a new theory of the human mind which powerfully addresses key areas of human conflict such as the ideological conflict between nations, the conflict in close relationships and the conflict between science and religion.